Cameras to the people: Reclaiming local histories and restoring environmental justice in community based forest management through participatory video (Alternautas, 2016)
Indigenous peoples’ histories and memories are almost invisible to the eyes and ears of western civilization. When we do hear about them, we generally do so through accounts and reconstructions made by naturalists, priests, explorers and more recently historians, geographers, and anthropologists – rarely from indigenous people themselves. Yet indigenous peoples in Latin America are very much aware that an important part of their struggle for cultural and physical survival involves telling the world their own histories. This post discusses how “participatory video” (PV) can help with indigenous peoples’ needs for cultural reassertion as well as with creating opportunities for restoring environmental justice in their territories